Model of Political Party Financial Regulation in Post-Reformation Indonesia - Moch Andry W.W Mamonto; Andika Wahyudi Gani (Manunggal Halim Jaya, 2022)
One of the sine qua non in modern democracies is the existence of political parties. In the context of the Indonesian state administration, the important role of political parties is emphasized through the provision of important functions by amending the 1945 Constitution of the Republic of Indonesia. To carry out the important functions of political parties, access to money is needed, but in politics the role of money must be regulated to prevent the negative impact of money in democracy. This research is a normative legal research, descriptive-prescriptive in nature, focusing on examining primary and secondary legal materials, using a statutory and conceptual approach. Since the beginning of the reformation period in the general elections of 1999, 2004, 2009, and 2019, the financial regulation of political parties in Indonesia has followed a prescription model, which is a regulatory model that issues orders and dictates the sources of revenue for political parties but does not regulate or dictate the use of political party funds. Efforts to maximize political parties' financial arrangements in order to ensure their independence and strengthen the principle of accountability begin by reformulating the regulation of funding sources from the state budget by adopting in-kind assistance, such as advertising prior to the general election to all parties participating in the general election.